Modeling the effect of 1 MeV electron irradiation on the performance of n(+)-p-p(+) silicon space solar cells - Hamache, Abdelghani; Sengouga, Nouredine; Meftah, Afak; Henini, Mohamed (Elsevier, 2016)
Energetic particles such as electrons and protons induce severe degradation on the performance of solar cells used to power satellites and space vehicles. This degradation is usually attributed to lattice damage in the active region of the solar cell. One of the phenomena observed in silicon solar cells exposed to 1 MeV electron irradiation is the anomalous degradation of the short circuit current. It initially decreases followed by a recovery before falling again with increasing electron fluence. This behavior is usually attributed to type conversion of the solar cell active region. The other figures of merit, on the other hand, decrease monotonically. In this work numerical simulator SCAPS (Solar Cell Capacitance Simulator) is used to elucidate this phenomenon. The current-voltage characteristics of a Si n+–p–p+ structure are calculated under air mass zero spectrum with the fluence of 1 MeV electrons as a variable parameter. The effect of irradiation on the solar cell is simulated by a set of defects of which the energy levels lie deep in energy gap of silicon (much larger than the characteristic thermal energy kT far from either the conduction or valence band). Although several types of deep levels are induced by irradiation including deep donors (exchange electrons mainly with the conduction band), deep acceptors (exchange electrons mainly with the valence band) and/or generation recombination centers (exchange electrons with both the conduction and valence bands), it was found that, only one of them (the shallowest donor) is responsible for the anomalous degradation of the short circuit current. It will be also shown, by calculating the free charge carrier profile in the active region, that this behavior is not related to type conversion but to a lateral widening of the space charge region.